Angular Dependence and Spatial Distribution of Jupiter's Centimeter‐Wave Thermal Emission From Juno's Microwave Radiometer. Issue 11 (20th November 2020) - Oyafuso, Fabiano; Levin, Steven; Orton, Glenn; Brown, Shannon T.; Adumitroaie, Virgil; Janssen, Michael; Wong, Michael H.; Fletcher, Leigh N.; Steffes, Paul; Li, Cheng; Gulkis, Samuel; Atreya, Sushil; et al.
Abstract: NASA's Juno spacecraft has been monitoring Jupiter in 53‐day orbits since 2016. Its six‐frequency microwave radiometer (MWR) is designed to measure black body emission from Jupiter over a range of pressures from a few tenths of a bar to several kilobars in order to retrieve details of the planet's atmospheric composition, in particular, its ammonia and water abundances. A key step toward achieving this goal is the determination of the latitudinal dependence of the nadir brightness temperature and limb darkening of Jupiter's thermal emission through a deconvolution of the measured antenna temperatures. We present a formulation of the deconvolution as an optimal estimation problem. It is demonstrated that a quadratic expression is sufficient to model the angular dependence of the thermal emission for the data set used to perform the deconvolution. Validation of the model and results from a subset of orbits favorable for MWR measurements is presented over a range of latitudes that cover up to 60° from the equator. A heuristic algorithm to mitigate the effects of nonthermal emission is also described. Plain Language Summary: One of the instruments on the Juno spacecraft that is currently orbiting Jupiter every 53 days is the microwave radiometer (MWR). It has been sensing the atmosphere for the first time over a wide range of depths below the top‐most clouds, covering pressures from less than the Earth's surface pressure to several thousand times that value. This enables a deeper exploration than ever before of how winds distribute gases that can condense, such as water (as in the Earth's atmosphere) and ammonia (which forms Jupiter's highest level clouds). One challenge in understanding the MWR data is to convert each of its raw measurements into an estimate of the true brightness temperature of Jupiter as though it were observed in a perfect, narrow beam, a process known as a deconvolution. We determined that this correction for the angular dependence can be done reliably with a three‐term (quadratic) expression. The results of this approach have formed the basis of all of the analysis of MWR data to date, and we show some of the intriguing results from orbits that allowed for the best MWR observing geometry over latitudes that cover up to 60° from the equator. Key Points: A method to deconvolve Jupiter's thermal emission measured by the Juno microwave radiometer is presented and validated Deconvolved nadir brightness temperatures and limb darkening results are presented for Juno observations between July 2016 and April 2018